2022
DOI: 10.1007/s40670-022-01554-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Virtual and In-Person Delivery of Mindfulness-Based Skills Within Healthcare Curriculums

Abstract: Purpose To promote well-being, healthcare education programs have incorporated mindfulness-based skills and principles into existing curriculums. Pandemic-related restrictions have compelled programs to deliver content virtually. Study objectives were to determine (1) whether teaching mindfulness-based skills within physician assistant (PA) programs can promote well-being and (2) whether delivery type (virtual vs. in-person) can impact the effectiveness. Methods During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…15 The size of the groups may have in itself negatively affected the therapeutic benefit that participants were receiving by reducing their time and attention from the MORE instructor while attending weekly sessions. Although virtually delivered MBIs have been shown to be efficacious, 10,21,30,33,38,43,55,73,74 this study encountered challenges with the virtual delivery of MORE. If we are to recognize the therapeutic effect of groups 52 and the microinteractions that make those groups into successful communities, it is important to recognize that virtual psychotherapy programs lack the opportunity for participants to connect when not directly engaged in group discussion and teaching by the facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…15 The size of the groups may have in itself negatively affected the therapeutic benefit that participants were receiving by reducing their time and attention from the MORE instructor while attending weekly sessions. Although virtually delivered MBIs have been shown to be efficacious, 10,21,30,33,38,43,55,73,74 this study encountered challenges with the virtual delivery of MORE. If we are to recognize the therapeutic effect of groups 52 and the microinteractions that make those groups into successful communities, it is important to recognize that virtual psychotherapy programs lack the opportunity for participants to connect when not directly engaged in group discussion and teaching by the facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…With the rise of virtual programming during the COVID-19 pandemic this may be an option to investigate. Studies have shown virtual non-cancer mindfulness participants have seen equal levels of sleep improvement 29 and coping and well-being, 30 in comparison to in-person delivery. Despite this, the self-identified introverted participants in our study mentioned experiencing delayed benefits in mental health and a newfound sense of satisfaction from the program after they had completed it, suggesting that even for introverted participants encouraging them to join group sessions may still be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual curricula consisting of online videos, live instruction, and self-study modules were found to be effective in promoting well-being in physician assistants, interns, residents, and attendings at both community and academic health centers. 44-48 Additionally, medical students have shown interest in learning and practicing mindfulness during clinical rotations. 49 Rac & Chakravarti 50 have proposed eight recommendations on how to integrate mindfulness practices for education and student benefit into the medical school curriculum.…”
Section: Discussionmentioning
confidence: 99%